In situ synchrotron radiation measurements of orthorhombic phase formation in an advanced TiAl alloy with modulated microstructure. Issue 1760 (2nd February 2015) - Rackel, M.; Stark, A.; Gabrisch, H.; Schimansky, F.-P.; Schell, N.; Schreyer, A.; Pyczak, F.
ABSTRACT: New low aluminium high niobium TiAl alloys exhibit a nano scale modulated microstructure consisting of lamellae with a tweed substructure. These tweed like appearing lamellae are a modulated arrangement of at least two phases. One constituent of the crystallographic modulation in the lamellae is an orthorhombic phase, which is closely related to both the hexagonal α2 -Ti3 Al phase and the cubic B2 ordered βo -TiAl phase. In this study the nature and formation of this orthorhombic phase has been investigated by high-energy X-ray diffraction. Measurements have shown that the newly formed orthorhombic phase is structurally comparable to the O phase (Ti2 AlNb). It forms in the temperature range of 550 °C to 670 °C from the α2 phase by small atomic displacements and chemical reordering. The in situ experiments yielded information about the thermal stability of the orthorhombic phase. After dissolving at temperatures above 700 °C the phase can be re-precipitated by annealing within the temperature range of formation.